Thermo-mechanical coupling in constitutive modeling of dissipative materials. (August 2016) - Egner, Wladyslaw; Egner, Halina
Abstract: In the present paper a thermodynamics based constitutive modeling of coupled dissipative phenomena is discussed. In the proposed analysis special attention is paid to the problem of thermo-mechanical coupling in rate equations of thermodynamic conjugated forces. As an example of thermo-plastic coupling, the non-isothermal fatigue behavior of tempered martensitic hot work tool steel is considered. The numerical simulations are performed, to illustrate the qualitative and quantitative influence of temperature rate on the response of constitutive model when cyclic thermo-mechanical loading is applied.